PENGARUH KONDISI KEUANGAN, AUDIT LAG, AUDIT TENURE, OPINION SHOPPING DAN AUDIT FEE TERHADAP OPINI AUDIT GOING CONCERN (Studi Empiris pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023) - Michael Febrian Sitorus; Dwi Ratmono (Diponegoro Journal of Accounting, 2025)
Economic uncertainty in Indonesia has caused most companies to experience problems related to their business continuity. Going concern opinions are believed to be a signal of such business continuity problems. This study aims to empirically prove the effect of financial condition, audit lag, audit tenure, opinion shopping, and audit fees on the acceptance of going concern opinions.This research used non-financial sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021-2023. The sample selection uses purposive sampling with a total of 441 observation data samples. The research analysis method uses logistic regression analysis with the assistance of E-Views 12 software.The results indicates that financial condition has a negative effect on the acceptance of going concern audit opinions. Meanwhile, audit lag, audit tenure, opinion shopping, and audit fees do not influence the acceptance of going concern opinions.